The Optimizing Contextual Human Resource Management to Enhance Operational Effectiveness: Evidence from a Community-Based Hospitality Business - Amrullah; Muhammad Adi Junaidi (Sumber Belajar Sejahtera, 2026)
This study examines strategies for optimizing human resource management (HRM) to enhance operational effectiveness in a community-based hospitality enterprise, Peraja Coffee and Bungalow, located in East Lombok. Using a qualitative case study approach, data were collected through in-depth interviews, participatory observation, and document analysis involving six key informants representing managerial and operational roles. The data were analyzed thematically through systematic coding, categorization, and interpretation. The findings reveal that HRM practices are predominantly informal yet highly adaptive, characterized by community-based recruitment, on-the-job training, and trust-based performance evaluation. Career development is facilitated through internal mentoring and social recognition rather than formal promotion systems, which effectively strengthens employee motivation, loyalty, and retention. This study contributes theoretically by extending contextual HRM literature through empirical evidence from a rural, community-based hospitality setting, highlighting how social values and participatory culture can function as strategic HRM mechanisms. Practically, the findings offer actionable insights for medium-scale hospitality enterprises, particularly in developing regions, on how integrating social capital with professional HRM practices can improve operational effectiveness and support long-term business sustainability.